“Disputas de origen: Américo Castro y la institucionalización de la filología en la Argentina” - Degiovanni, Fernando; Toscano y García, Guillermo (El Colegio de México, 2010)
This article revises the process of institutionalization of philology in Argentinathrough the study of a number of documents unknown to date: the letterssent by Américo Castro, the first director of the Institute of Philologyat the University of Buenos Aires, to Ramón Menéndez Pidal and TomásNavarro Tomás, of the Center for Historical Studies in Madrid. The analysisof this material demonstrates that the foundation of the Institute involvedthe articulation of competing views concerning the definition of its institutionalagenda. The cultural discourses of nationalism and Hispanism, aswell as some preestablished notions on the relationship betwee specializedknowledge and society, triggered a series of conflicts between the Center’spolitical and cultural aims, and the Argentine interests surrounding theconstitution of the discipline.